1992
DOI: 10.1016/0735-1097(92)90018-i
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of sinus node disease treated with atrial pacing in 213 patients: Implications for selection of stimulation mode

Abstract: In sinus node disease, atrial pacing can be successfully applied during long-term follow-up. Patients with complete bundle branch or bifascicular block in addition to sinus node disease should initially receive a dual-chamber pacemaker, but routine application of dual-chamber stimulation does not appear to be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
5
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(52 citation statements)
references
References 30 publications
2
44
5
1
Order By: Relevance
“…Even development of chronic AF does not subject the atrially paced patients to a mode change to ventricular demand, as long as ventricular response is adequate. 8,10,24) This was shown in one of our patients. In fact, there are arguments that development of stable AF indicates an end stage of sick sinus syndrome and provides a self cure of this disease.17, However, the development and persistence of atrial fibrillation may still present an obstacle to maximal medical control of heart rate in the absence of electrical ventricular support in patients paced atrially only.…”
Section: Discussionsupporting
confidence: 75%
“…Even development of chronic AF does not subject the atrially paced patients to a mode change to ventricular demand, as long as ventricular response is adequate. 8,10,24) This was shown in one of our patients. In fact, there are arguments that development of stable AF indicates an end stage of sick sinus syndrome and provides a self cure of this disease.17, However, the development and persistence of atrial fibrillation may still present an obstacle to maximal medical control of heart rate in the absence of electrical ventricular support in patients paced atrially only.…”
Section: Discussionsupporting
confidence: 75%
“…28) Despite all the studies suggesting a disadvantage of VVI mode, a few randomized, controlled study has been performed. [27][28][29] Although the Canadian Trial of Physiologic Pacing (CTOPP) 30) did not show benefit of physiologic pacing on overall mortality, CTOPP reported an 18% reduction (6.6% annual rate with ventricular pacing vs 5.3% with physiological pac- In this case, atrial fibrillation was started followed by single PAC.…”
Section: ) Pacing Mode Selectionmentioning
confidence: 85%
“…[25][26][27] In our series, the long-term evaluation of the development of persistent AF and recurrence of paroxysmal AF were studied in 70 patients with a history of AF before pacemaker implantation. In a mean follow-up of 8 years, the incidence of chronic AF was 78% in the patients undergoing VVI pacing compared with 45% in DDD pacing and recurrence rate of paroxysmal AF was 93% in VVI pacing and 58% in DDD pacing.…”
Section: ) Pacing Mode Selectionmentioning
confidence: 99%
“…Any pacemaker reoperation is associated with a 2% risk of device infection, with a potential need to extract the complete pacemaker system [11,12]. Some studies showed that bundle branch block, bifascicular block [13], or Wenckebach block point lower than 120 beats/min [14] were predictive for the development of advanced atrioventricular block. However, some other studies presented opposing results [15,16].…”
Section: Streszczeniementioning
confidence: 99%